Kualitas Pelayanan dalam Pembuatan Surat Keterangan Kependudukan - Hulu, Petra Saprialdi; Karlina, Nina (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This research aims to find out how much service quality is achieved in making population certificates in Mekarsari Village, Cikajang District, Garut Regency. In this research, the author uses the SERVQUAL (Service Quality) theory with 5 dimensions, namely tangible, reliability, responsiveness, assurance, and empathy. The method used is descriptive with a quantitative approach. The results of this research show that the quality of service in making population certificates in Mekarsari Village, Cikajang District, Garut Regency, based on the tangible dimension, is in the good category, while the dimensions of reliability, responsiveness, assurance and empathy are in the very good category. Overall, the results obtained from the average calculation for all SERQUAL dimensions were 3.10, which means it is in the very good category. In conclusion, all service activities in making population certificates in Mekarsari Village have been running very well and can provide quality services to the community because the service in making population certificates is quite simple, including the process, completeness and file requirements as well as the costs required. and the time required is also not long Keywords: Service Quality, Mekarsari Village Government, Population Certificate